Allergen Exposure: When Timing Is Everything - Mahlakõiv, Tanel; Artis, David (Immunity (Cambridge, Mass.), 2016)
It is known that young children exposed to allergens are prone to develop asthma later in life. In this issue of Immunity, de Kleer et al. (2016) identify IL-33 as a key player in the developing lung for sensitization to environmental allergens and airway hyperreactivity. It is known that young children exposed to allergens are prone to develop asthma later in life. In this issue of Immunity, de Kleer et al. (2016) identify IL-33 as a key player in the developing lung for sensitization to environmental allergens and airway hyperreactivity.